EZ wheel's lugnut fastener / Ali Imran Hamzah ... [et al.] - Hamzah, Ali Imran; Muzafar, Mohamad Ashraf; Syed Mustaffa, Syed Izzat Afiq; Mohd Zali, Muhammad Izham Hakimi
A lug nuts may be removed using a lug, socket or impact wrench on it. If the wheel is to be removed then an automotive jack to raise the vehicle and some wheel chocks would be used as well. But in order to remove the nut from the tire portably and more on the efficiency, creating a new type of lug nut opener in innovative ways are really promising. Lug nuts can be difficult to remove, as they may become frozen to the wheel stud. In such cases a breaker bar or repeated blows from an impact wrench can be used to free them. Alternating between tightening and loosing can free especially stubborn lug nuts. Lug nuts must be installed in an alternating pattern, commonly in Malaysia, it was referred to as a cross pattern. This ensures a uniform distribution of load across the wheel mounting surface. When installing lug nuts, it is recommended to tighten the with a calibrated torque wrench. While a lug, socket or impact wrench may be used to tighten lug nuts the final tightening should be performed by a torque wrench, ensuring an accurate load is applied. Many things must considered in order to build something technical. Additionally, under tightened lug nuts may come loose with time. Safety measures accursed during this designation so that it is become more ergonomically and user friendly. Furthermore it is designed for all types of driver, especially women driver in this country